Improving science observation skills through "Nature Hunt Guided Inquiry" in children aged 4–5 years - Sari, Nurmaya; Andi Ali Kisai; Aip Syarifudin (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: Science observation skills are essential for developing science literacy in early childhood. However, preliminary observations at PAUD Bunga Bangsa Cirebon revealed that children aged 4–5 years experienced difficulties in focusing attention, recognizing object characteristics, distinguishing objects, and communicating their observations. Objective: This study aimed to improve the science observation skills of children aged 4–5 years through the implementation of Nature Hunt Guided Inquiry. Methods: This study employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles involving 20 children aged 4–5 years from Group A2. Data were collected through observation and documentation and analyzed using quantitative and qualitative descriptive techniques. Results: The implementation of Nature Hunt Guided Inquiry effectively improved children's science observation skills. The percentage of mastery increased from 20% (4 children) in the pre-action stage to 55% (11 children) in Cycle I and reached 85% (17 children) in Cycle II, indicating an improvement of 65 percentage points. Conclusion: Nature Hunt Guided Inquiry is effective in improving the science observation skills of children aged 4–5 years through structured and meaningful environmental exploration activities.